Pengaruh Media Pembelajaran Audio Visual Terhadap Hasil Belajar IPA di Kelas V MI Muhammadiyah Tegalurung - Muzfirah, Suci; Fitriyani, Anis; Oktaviani, Nuni (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research wa motivated by improving science learning outcomes in class V of MI Muhammadiyah Tegalurung. So far, the teaching and learning process has only been carried out conventionally, such as lecturing, taking notes from the blackboard written by the teacher withous using learning media. To improve science learning outcomes, you need to use the right methods and media, one of which is using tools in the from of audio-visual media. This research aims to determine the effect of audio-visual media on science learning outcomes in class V MI Muhammadiyah Tegalurung. This research uses a quantitative method with a pre-experimental design type in the form of a one shot case study, namely an experiment that only involves one experimental class without a comparison class (control) and is carried out pnly using the final test, namely the test after the experimental class is given treatment (posttest). The subjects of this research were 26 students as a trial class for using audio-visual media. In taking samples, this research used the Non-Probability sampling technique with a purposive sampling model. The results of this research indicate that the use of audio-visual media is effective in class V MI Muhammadiyah Tegalurung, which can be seen from the R square value of 0,390 or 39%. The average value of science learning outcomes is 82,1. With a standard devination of 6,1. From these results, there were 25 students (96,16%) who had achieved the minimum completeness score (KKM) and 1 student (3,84%) had not reached the minimum completeness score (KKM). The results of data analysis using the t test with a significance of 0,05 are tcount 3,913 which is greater than ttabel 1,705. So it can be concluded that Ha is accepted and Ho is rejected. This means that the use of audio visual media influences science learning outcomes in class V MI Muhammadiyah Tegalurung.